2018
DOI: 10.1016/j.bcp.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The structural determinants of the bitopic binding mode of a negative allosteric modulator of the dopamine D 2 receptor

Abstract: SB269652 is a negative allosteric modulator of the dopamine D receptor (DR) yet possesses structural similarity to ligands with a competitive mode of interaction. In this study, we aimed to understand the ligand-receptor interactions that confer its allosteric action. We combined site-directed mutagenesis with molecular dynamics simulations using both SB269652 and derivatives from our previous structure activity studies. We identify residues within the conserved orthosteric binding site (OBS) and a secondary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 37 publications
1
35
1
2
Order By: Relevance
“…More comprehensive analyses of the D2R mutants by collecting full ONC201 doseresponse curves using Go activation and cAMP inhibition assays showed that mutations of four specific residues, V91 2.61 , E95 2.65 , Y192 5.41 , and I397 6.59 , produced the most severe impact on ONC201's ability to antagonize dopamine-stimulated signaling. Notably, two of these residues, V91 2.61 and E95 2.65 , reside within a SBP formed by the interface between TMs 2 and 7 and have been shown to be involved in allosteric modulation of the D2R by bitopic and negative allosteric modulators (NAMs) (Draper-Joyce et al, 2018;Klein Herenbrink et al, 2019;Verma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More comprehensive analyses of the D2R mutants by collecting full ONC201 doseresponse curves using Go activation and cAMP inhibition assays showed that mutations of four specific residues, V91 2.61 , E95 2.65 , Y192 5.41 , and I397 6.59 , produced the most severe impact on ONC201's ability to antagonize dopamine-stimulated signaling. Notably, two of these residues, V91 2.61 and E95 2.65 , reside within a SBP formed by the interface between TMs 2 and 7 and have been shown to be involved in allosteric modulation of the D2R by bitopic and negative allosteric modulators (NAMs) (Draper-Joyce et al, 2018;Klein Herenbrink et al, 2019;Verma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reveal that the bitopic ligand strategy can provide improved receptor subtype selectivity, affinity, and functional selectivity [ 37 , 38 , 39 ]. Additionally, bitopic ligands can also confer unique receptor signaling an example of which is the bitopic ligand SB269,652 that behaves as an allosteric antagonist at D 3 Rs and D 2 Rs [ 40 , 41 ]. Indeed, we have successfully utilized a bitopic design strategy to synthesize potent, selective, and G protein biased full agonists at D 2 R [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 In particular, a cluster of residues in transmembrane segment 2, including V91, L94, and E95, has been found to mediate important contacts between the ligand and the secondary binding pocket. 18 20 …”
Section: Introductionmentioning
confidence: 99%